Relation between child maltreatment and human capital: results from a population-based birth cohort - Roberta Hirschmann; Cauane Blumenberg; Pedro San Martin Soares; Ana Maria Baptista Menezes; Fernando César Wehrmeister; Helen Gonçalves (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: This study aimed to investigate the association between child maltreatment and human capital, measured by intelligence quotient (IQ) at age 18 years and schooling at age 22 years in 3,736 members from a population-based birth cohort in Southern Brazil. A multiple linear regression was used to assess the association between child maltreatment and human capital measurements. Physical and emotional abuse and physical neglect occurring up to 15 years of age were considered child maltreatment. Physical neglect was associated with lower IQ scores in women (β = -4.40; 95%CI: -6.82; -1.99) and men (β = -2.58; 95%CI: -5.17; -0.01) and lower schooling for all sexes: women (β = -1.19; 95%CI: -1.64; -0.74) and men (β = -0.82; 95%CI: -1.34; -0.30). Moreover, men who had experienced one type of child maltreatment and women who had experienced two or more types had lower years of schooling at 22 years (β = -0.41; 95%CI: -0.73; -0.89 and β = -0.57; 95%CI: -0.91; -0.22, respectively) than those who suffered no kind of maltreatment. Efforts to improve future educational and cognitive outcomes must include early prevention and intervention strategies for child maltreatment.